Implementation of Criminal Liability for Companies That Do Not Fulfill Obligations to Workers in Employment BPJS Guarantee - Moh. Fahrul Dawali; Lisnawati W. Badu; Suwitno Y. Imran (Universitas Negeri Gorontalo, 2022)
This study aims to determine and analyze the criminal liability of companies that do not fulfill their obligations to workers in the employment BPJS guarantee. The research method used is sociological juridical research, using a descriptive qualitative research approach and interactive analysis techniques. The results of this study indicate that there are still many companies that neglect to provide fulfillment of workers' obligations in the Employment BPJS guarantee as stipulated in Law No. 24 of 2011 concerning the Social Security Organizing Agency (Law No. 24 of 2011), which protects workers' rights to obtain guarantees for compensation for work accidents. The establishment of the Social Security Organizing Agency (BPJS) is not a new thing in the field of employment, because social security for workers has previously been regulated in Law No. 14 of 1993 concerning Workers' Social Security or better known as Jamsostek. Law No. 40 of 2004 on the National Social Security System was enacted in 2004 with the aim of creating an integrated social security system for all Indonesians, and the social security system was institutionalized in a public legal entity.